(untitled) (Cultura Económica, 2025)
In the following article I would like to present an alternative explanation to the various theses that have been proposed regarding the so-called crisis of contemporary liberalism (Sloterdijk, Deneen, Levitsky and Ziblatt, etc.). I would like to specifically analyze the contemporary Western social and political situation (taking the term "Western" in a broad sense) using the conceptual framework proposed by the Neapolitan Giambattista Vico. After a preliminary review of some of the ideas he proposes in his book Scienza Nuova, I would like to try to explain the current political situation using his theoretical framework. In my view, Vico’s ideas are very useful to get a better understanding of the contemporary political situation.